Zhinao Capsule improves learning and memory impairment in APP/PS1 mice through gut–brain axis-mediated inhibition of neuroinflammation - Fang, Shuzhen; Xi, Hu; Zhang, Kangyi; Fang, Xiang; Yang, Yulong; Li, Jing; Yang, Wenming (Frontiers in Microbiology, 2026)
Traditional Chinese Medicine (TCM) interventions have attracted increasing attention in recent years, with a growing body of evidence supporting their efficacy in the treatment of Alzheimer’s disease (AD). Zhinao Capsule (ZNJN), a proprietary TCM formulation, has demonstrated promising clinical outcomes, particularly in enhancing cognitive function and alleviating AD-related pathology in rodent models. This study aimed to evaluate the neuroprotective effects of ZNJN in APP/PS1 transgenic mice. Behavioral assessments indicated that ZNJN, especially at the high dose, significantly improved learning and memory abilities. Histopathological analysis revealed a marked reduction in hippocampal Aβ1–42 deposition and decreased activation of microglia and astrocytes, as evidenced by lower expression levels of Iba-1 and GFAP. In addition to central effects, ZNJN alleviated colonic inflammation and improved mucosal integrity. Systemic inflammatory responses were also suppressed, with significant reductions in serum levels of TNF-α, IL-6, IL-1β, and LPS. Furthermore, 16S rRNA gene sequencing showed that ZNJN modulated the gut microbiota by decreasing the abundance of pro-inflammatory genera and enriching potentially beneficial. These findings suggest that ZNJN exerts neuroprotective effects by modulating the gut microbiota and reducing neuroinflammation through the gut–brain axis. These findings suggest that ZNJN exerts neuroprotective effects by modulating the gut microbiota and reducing neuroinflammation through the gut–brain axis. This study provides experimental evidence supporting the potential of ZNJN as a multi-target therapeutic agent for AD intervention.